2004
DOI: 10.1073/pnas.0403140101
|View full text |Cite
|
Sign up to set email alerts
|

Targeted knockout in Physcomitrella reveals direct actions of phytochrome in the cytoplasm

Abstract: The plant photoreceptor phytochrome plays an important role in the nucleus as a regulator of transcription. Numerous studies imply, however, that phytochromes in both higher and lower plants mediate physiological reactions within the cytoplasm. In particular, the tip cells of moss protonemal filaments use phytochrome to sense light direction, requiring a signaling system that transmits the directional information directly to the microfilaments that direct tip growth. In this work we describe four canonical phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
88
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 42 publications
1
88
0
Order By: Relevance
“…The Pp.phy4 knockout line was as described (18). Double and triple phototropin knockout lines were kindly donated by Masahiro Kasahara (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pp.phy4 knockout line was as described (18). Double and triple phototropin knockout lines were kindly donated by Masahiro Kasahara (22).…”
Section: Methodsmentioning
confidence: 99%
“…Neochromes are, however, absent from mosses and higher plants. Indeed, targeted knockout in the moss Physcomitrella patens showed that a canonical phytochrome Pp.phy4 was responsible for vectorial responses including phototropism, polarotropism, and chloroplast relocation (18). We were thus interested in how this and perhaps higher plant phytochromes might provide an appropriate signal within the cytoplasm.…”
mentioning
confidence: 99%
“…Because such a gene sequence is also absent from the extensive moss EST and nearly complete Physcomitrella genome databases, it is very unlikely that an Adiantum PHY3 homolog is present in mosses. In any case, targeted knockout of PHY and PHOT genes in Physcomitrella has shown that red-light-induced chloroplast movement in Physcomitrella is mediated by canonical phys with phots acting downstream (6,7).…”
mentioning
confidence: 99%
“…Data from gene-targeted phytochrome knockout mutants in Physcomitrella patens and Ceratodon purpureus further supports the role of these red-light sensors in phototropism (14,15). Relocation of chloroplasts in nonvascular plants is also controlled by phytochromes, neochromes and phototropins (14,16,17). For these photoresponses, cytosolic photosensors are required to sense the light direction.…”
mentioning
confidence: 89%
“…The protonema grows toward unilateral red light (positive phototropism) at high fluence rates (5-10 μmol m −2 s −1 ), away from it (negative phototropism) at low fluence rates (below 1 μmol m −2 s −1 ), and spreads randomly at intermediate fluence rates (25). Phytochromes have been implicated as the main photoreceptor sensing light direction in control of protonemal cell growth in Physcomitrella (14). To test the hypothesis that both FDBRs contribute to the red-light-phototropic response, we analyzed the red-light triggered phototropic response in single and double mutants.…”
mentioning
confidence: 99%